if Ax + b = 0, then x = -b/a
This is not a huge surprise. They probably teach this to high school kids.
But until today, when faced with an equation like the one above, I would do it step by step, like so:
2x + 3 = 0
2x = -3
x = -3/2
Of course I'm not a yukel. I noticed that the constant term always ended up being the numerator and that the coefficient ended up being the denominator. I just never thought about it long enough to start using a formula to solve equations instead of the step-by-step approach.
So I guess the point of this post is that today I thought of something which there's no excuse for me not thinking of before.